Determinants of Financial Reporting Local Government Organization Transparency and Accountability as a Mediator - Nazaruddin, Ietje; Rahmandani, Yustisia Melasari; Sibuea, Salsabila Putri Aryati (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 2 (2023), 2023)
This study examines the role of accountability as a mediating variable in understanding how internal control and external pressure influence financial reporting transparency. Data was sourced from a survey, garnering responses from 214 participants. The purposive sampling technique was adopted, focusing on responses from heads of finance departments, financial treasurers, and financial staff supporting local government organizations (OPD). For hypothesis testing, the study employed Structural Equation Modeling (SEM) grounded on the Partial Least Squares (PLS) approach. Results revealed that internal control significantly promotes financial reporting transparency in OPD, with accountability serving as a mediator. In contrast, external pressure alone is inadequate to guarantee the transparency and accountability of financial reports within local governments. Consequently, OPDs are advised to bolster their internal control and accountability mechanisms to enhance the trustworthiness of their financial statements. Keywords: internal control, external pressure, accountability, and financial reporting transparency